2015
DOI: 10.1037/abn0000092
|View full text |Cite
|
Sign up to set email alerts
|

Elevated striatal reactivity across monetary and social rewards in bipolar I disorder.

Abstract: Bipolar disorder (BD) is associated with increased reactivity to rewards and heightened positive affectivity. It is less clear to what extent this heightened reward sensitivity is evident across contexts and what the associated neural mechanisms might be. The present investigation employed both a monetary and social incentive delay task among adults with remitted BD type I (N=24) and a healthy non-psychiatric control group (HC; N=25) using fMRI. Both whole-brain and region-of-interest analyses revealed elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 96 publications
1
44
0
Order By: Relevance
“…Interestingly however, we did see a relationship between more severe mania symptoms and greater bias towards reward, but only among individuals with bipolar disorder with lifetime psychosis. This finding is consistent with prior work in bipolar disorder suggesting increased striatal responses to rewards (Dutra, Cunningham, Kober, & Gruber, 2015), and with theories about reward hypersensitivity as a risk factor and/or characteristic of bipolar disorder (Alloy, Nusslock, & Boland, 2015; Johnson, Edge, Holmes, & Carver, 2012a). It is intriguing that we only saw this relationship among individuals with bipolar disorder with psychosis and not in schizophrenia or schizoaffective.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly however, we did see a relationship between more severe mania symptoms and greater bias towards reward, but only among individuals with bipolar disorder with lifetime psychosis. This finding is consistent with prior work in bipolar disorder suggesting increased striatal responses to rewards (Dutra, Cunningham, Kober, & Gruber, 2015), and with theories about reward hypersensitivity as a risk factor and/or characteristic of bipolar disorder (Alloy, Nusslock, & Boland, 2015; Johnson, Edge, Holmes, & Carver, 2012a). It is intriguing that we only saw this relationship among individuals with bipolar disorder with psychosis and not in schizophrenia or schizoaffective.…”
Section: Discussionsupporting
confidence: 91%
“…In an earlier analysis of these data, we found that the VS exhibited elevated reactivity to reward receipt in euthymic BD, compared to an HC group . Notably, no task‐related differences in VS reactivity to reward receipt emerged.…”
Section: Introductionmentioning
confidence: 68%
“…Efforts to better understand these behavioral patterns at the neural level have primarily focused on regional neural activity during reward tasks. For example, studies have reported increased activation in the ventral striatum (VS) and orbitofrontal cortex (OFC) of patients with BD compared to healthy controls (HCs) during reward processing. While these data provide an important foundation, they cannot fully explain the pathophysiology of reward processing dysfunctions in BD, as these regions do not operate independently but interact as components of complex neural networks .…”
Section: Introductionmentioning
confidence: 99%
“…Also consistent with trait status for reward hypersensitivity in BSDs, individuals with euthymic bipolar I (Nusslock, Almeida, et al, 2012) and bipolar II (Caseras et al, 2013) disorders displayed greater VS, medial OFC (Brodmann area [BA] 10), and left lateral OFC (BA 47) activation during anticipation of monetary rewards compared to healthy controls, and elevated VS activation in euthymic bipolar I individuals extends to social rewards as well (Dutra, Cunningham, Kober, & Gruber, 2015). Moreover, Trost et al (2014) found that euthymic bipolar I patients exhibited decreased suppression of reward-related activation in the reward circuit when they had to reject immediate reward in favor of a long-term goal on the “desire-reason dilemma” task (Diekhof & Gruber, 2010) compared to healthy controls.…”
Section: Reward Hypersensitivity In Bipolar Spectrum Disorders: Theormentioning
confidence: 87%